Fluid Sucralphate in Post Esophageal Varices Ligation Esophageal Ulcer - Marcellus Simadibrata; Syarif Hidayat; Chudahman Manan (The Indonesian Society for Digestive Endoscopy, 2002)
Background: One of the complications of esophageal varices ligation is deep ulcer. Sucralphate has been shown to prevent and heal post ligation esophageal ulcer. Materials and method: All patients with liver cirrhosis and portal hypertension undergoing esophageal varices ligation in the year 2000/2001 were included in this study. Using “double-blind random sampling”, patients were divided into 2 groups, those receiving sucralphate and those receiving placebo for 2 weeks. Endoscopy of the upper gastrointestinal tract was conducted regularly on the 7th, 10th, and 14th day to evaluate the diameter of the esophageal ulcer based on the diameter of forceps biopsy. The data were evaluated using analysis of variance (ANOVA) or kruskal wallis. Results: Statistically, there was no significant difference in the characteristics of group A patients receiving sucralphate and group B patients receiving placebo. Only 17 patients from group A and 20 from group B were allowed to participate in this study. On the 10th day, the average diameter of the esophageal ulcer in the sucralphate group was significantly smaller than that from the placebo group. (4.74 + 2.02 mm vs 5.42 + 2.22 mm; p=0.04). On the 14th day, the average diameter of esophageal ulcer in the sucralphate group was also significantly less than that of the placebo group (0.88 + 1.58 vs 2.99 + 2.04 mm; p < 0.01). Conclusion:Sucralphate is able to accelerate post esophageal varices ligation esophageal ulcer. Keywords: sucralphate, esophageal ulcer, esophageal varices ligation